HUBUNGAN KEMAMPUAN BERPIKIR KRITIS PADA MAHASISWA MELALUI PENGGUNAAN MEDIA SOSIAL DALAM PENDIDIKAN - Imamudin, Imamudin; Fahmi, Rizal; Saepudin, Saepudin; Setiawardani, Wawan (JIPIS, 2023)
In this digital era, the development of science and technology not only brings change and convenience in the way of human life, but also brings changes to the mindset of today's society. This research was conducted with the aim of finding out the relationship between students' critical thinking skills through the use of social media in education. Based on existing studies, unfortunately many young people, especially students, still underestimate the need for critical thinking skills. The methodology in this study uses a literature study or literature study. Unfortunately, many young people, especially students, still underestimate the need for critical thinking skills. The results of the study ensure that students' critical thinking skills through the use of social media in education have a close relationship and a support system is also needed that can provide encouragement and motivation to pursue desires and have the desired abilities.